Combined mass-dependent and nucleosynthetic isotope variations in refractory inclusions and their mineral separates to determine their original Fe isotope compositions. (15th October 2019) - Shollenberger, Quinn R.; Wittke, Andreas; Render, Jan; Mane, Prajkta; Schuth, Stephan; Weyer, Stefan; Gussone, Nikolaus; Wadhwa, Meenakshi; Brennecka, Gregory A.
Abstract: Calcium-aluminum-rich inclusions (CAIs) are the oldest dated materials that provide crucial information about the isotopic reservoirs present in the early Solar System. For a variety of elements, CAIs have isotope compositions that are uniform yet distinct from later formed solid material. However, despite being the most abundant metal in the Solar System, the isotopic composition of Fe in CAIs is not well constrained. In an attempt to determine the Fe isotopic compositions of CAIs, we combine extensive work from a previously studied CAI sample set with new isotopic work characterizing mass-dependent and mass-independent (nucleosynthetic) signatures in Mg, Ca, and Fe. This investigation includes work on three mineral separates of the Allende CAI Egg 2. For all isotope systems investigated, we find that in general, fine-grained CAIs exhibit light mass-dependent isotopic signatures relative to terrestrial standards, whereas igneous CAIs have heavier isotopic compositions relative to the fine-grained CAIs. Importantly, the mass-dependent Fe isotope signatures of bulk CAIs show a range of both light (fine-grained CAIs) and heavy (igneous CAIs) isotopic signatures relative to bulk chondrites, suggesting that Fe isotope signatures in CAIs largely derive from mass fractionation events such as condensation and evaporation occurring in the nebula. Such signatures show that a significant portion of the secondary alteration experienced by CAIs, particularly prevalent in fine-grained inclusions, occurred in the nebula prior to accretion into their respective parent bodies. Regarding nucleosynthetic Fe isotope signatures, we do not observe any variation outside of analytical uncertainty in bulk CAIs compared to terrestrial standards. In contrast, all three Egg 2 mineral separates display resolved mass-independent excesses in 56 Fe compared to terrestrial standards. Furthermore, we find that the combined mass-dependent and nucleosynthetic Fe isotopic compositions of the Egg 2 mineral separates are well correlated, likely indicating that Fe indigenous to the CAI is mixed with less anomalous Fe, presumably from the solar nebula. Thus, these reported nucleosynthetic anomalies may point in the direction of the original Fe isotope composition of the CAI-forming region, but they likely only provide a minimum isotopic difference between the original mass-independent Fe isotopic composition of CAIs and that of later formed solids.